The utilization of flashcard to enhance students’ writing performance: An action research - Muhammad Eko Saputro; Ulfa Amalia; Juhansar (Universitas Jambi, Indonesia, 2022)
The development of science and technology facilitates teachers to conduct their learning-teaching processes effectively. However, it does not mean that all conventional media are ineffective at all to be used in the learning-teaching processes. Therefore, this present research aimed to explore the utilization of flashcards as learning-teaching media to improve students' writing performance and to discover students' performance in writing English sentences through flashcards. This research applied action research, employing interviews, observation, and tests to collect qualitative and quantitative data. The qualitative data were analyzed using interpretations, while the quantitative data were analyzed using IBM SPSS version 24.0. The results of qualitative data showed that students were active, enthusiastic, diligent, brave, and motivated in writing English sentences using flashcards. Meanwhile, the quantitative data showed the mean score of the pre-test was 2,86; the post-test I was 3,14, and the post-test II was 3,89. The percentage was 10% from the pre-test to post-test I and 12% from the post-test I to the post-test II. It indicated that the scores and the mean in the post-test II were better than in the post-test I. It proved that using flashcards as a learning-teaching medium is sufficient to enhance students' performance in writing English sentences. This research recommends further research to discover the flashcard utilization in the learning-teaching processes at a different school or educational institution levels and conduct experimental research to seek the effectiveness of flashcards as a medium in t English writing learning-teaching processes.